How Do They Survive? Study On Small Businesses Survive Covid-19 In Semarang - Aryan Eka Prastya Nugraha; Dwi Prastyo Hadi; Valdyan Drifanda (Jurnal Manajemen Indonesia, 2021)
The purpose of this study is to analyze the factors that push small businesses to survive during the Covid-19 pandemic and the factors that influence it. The method used in this research is the Exploratory Factor Analysis (EFA) uses PLS-SEM with a moderating effect. A total of 162 small-scale business units in Semarang participated in this research by filling the online research instrument. The result of this study indicates that Business Performance, Government Policy, and Stress processes have a positive influence on Business Resilience. The process of maintaining a business is weakened by the characteristics of a business vulnerability that will continue to overshadow the owners to keep the business. It is hoped that small business owners in Semarang could improve business performance by expanding market orientation by producing goods that are at lower prices with the same quality and possibly reducing quantity. Input Materials must switch to using local raw materials even though the price is quite high compared to those that often used imported raw materials to continue to meet the basic needs of the community, such as in the grocery / wholesale business. As for small businesses to be able to survive, the government's participation amidst the threat of recession at this moment should come with more flexible policies, one of them is making policies on integration between SMEs that can be interconnected with one another to keep the demand and supply on the run. Besides, business owners must be able to do a variety of ways related to resource management that can do from the investment of resources and, most importantly, ready to prevent excessive loss of resources. Keywords—business resilience; small business; covid-19